The effect of pregnancy‐induced hypertensive disorders on placental growth along short and long axes and neonatal outcomes. (5th June 2015) - Phad, Neelkanth; Dahlstrom, Jane E.; Ellwood, David; Kent, Alison L.
<x xml:space="preserve">Abstract</x> Aim To assess the effect of pregnancy‐induced hypertensive disorders on the growth of the placenta on the short and long axes and neonatal outcomes. Materials and Methods A retrospective cohort study of gross and histological characteristics of placentas and the fetal outcomes of normotensive and hypertensive pregnancies over a three‐year period from January 2009 to December 2011 at a tertiary teaching hospital in ACT, Australia. Results Placentas and neonatal outcomes from 100 pregnancies complicated with pregnancy‐induced hypertension/pre‐eclampsia were studied and compared with 51 gestational age‐matched placentas and neonatal outcomes from normotensive pregnancies. The median maternal age and smoking history were similar in the two groups (P = 0.894; P = 1.00, respectively). The median pre‐pregnancy weight was significantly higher (P < 0.001) and primiparity more common (P = 0.001) in the study group. The median weight of the placenta was significantly lower (P < 0.001) and below the 10th centile (P < 0.001) in the study group. Both the long and short axes of the placental disc were significantly smaller in the study group (P = 0.002; P ≤ 0.001 respectively). Accelerated villous maturation, placental infarcts and decidual vessel vasculopathy were more common in the study group (P < 0.001). The median birthweight and the number of infants with birthweight and length below the 10th centile were significantly higher in the study group (P = 0.008; P < 0.001; P = 0.004, respectively). Conclusion This study demonstrates that pregnancy‐induced hypertension significantly influences the growth and development of both the placenta and fetus.